To simplify (2k+1)(k-4), we can use the distributive property:
(2k+1)(k-4) = 2k(k-4) + 1(k-4)
Now we can simplify each term separately:
2k(k-4) = 2k^2 - 8k
1(k-4) = k - 4
Putting the terms back together, we get:
(2k+1)(k-4) = 2k^2 - 8k + k - 4
Simplifying further:
(2k+1)(k-4) = 2k^2 - 7k - 4
To simplify (-2y+5)(y+3), we can again use the distributive property:
(-2y+5)(y+3) = -2y(y+3) + 5(y+3)
Simplifying each term separately:
-2y(y+3) = -2y^2 - 6y
5(y+3) = 5y + 15
Putting the terms back together:
(-2y+5)(y+3) = -2y^2 - 6y + 5y + 15
Simplifying further:
(-2y+5)(y+3) = -2y^2 - y + 15
What is the expression (2k+1)(k-4) and (-2y+5)(y+3) simplified?
1 answer